2014
DOI: 10.5489/cuaj.1682
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcomes of partial nephrectomy for tumours larger than 4 cm: A systematic review

Abstract: Introduction: Many medical associations recommend nephronsparing surgery (NSS) for tumours larger than 4 cm amenable to partial nephrectomy (PN). These recommendations are, however, mostly based on isolated reports. We systematically review the oncological outcomes of partial nephrectomy procedures performed for tumours larger than 4-cm. Methods: A PubMed search was carried out using keywords "partial nephrectomy" and "nephron sparing" for records dating back to 1995. In total, 2136 abstracts were analyzed; fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Overall survival (OS) was estimated to be 87,1% (T1b) and 74% (T2) respectively. The results are comparable to those achieved after radical nephrectomy with a significant advantage in terms of preservation of renal function [17].…”
Section: The Morbidity Of Radical Nephrectomysupporting
confidence: 70%
See 1 more Smart Citation
“…Overall survival (OS) was estimated to be 87,1% (T1b) and 74% (T2) respectively. The results are comparable to those achieved after radical nephrectomy with a significant advantage in terms of preservation of renal function [17].…”
Section: The Morbidity Of Radical Nephrectomysupporting
confidence: 70%
“…Overall survival (OS) was estimated to be 87,1% (T1b) and 74% (T2) respectively. The results are comparable to those achieved after radical nephrectomy with a significant advantage in terms of preservation of renal function [17].The issue of survival following RN and PN was addressed in an analysis of the SEER database from 1988 to 2003. A total of 2,399 patients with T1b renal tumours that underwent RN (91.5%) or PN (8.5%) were included in the analysis.…”
mentioning
confidence: 59%
“…However, the aim to preserve renal function as much as possible has triggered PN in larger tumors despite an increased surgical challenge and tumor size-related risk of progression and survival. From two recent reviews, it can be concluded that survival rates appear to be similar and renal function is better preserved for patients with cT1b renal cancers with PN versus RN [ 19 , 20 ]. However, current evidence is based on small case series and retrospective observational studies and confounding by indication might have played a role.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes are similar to those reported in historical radical nephrectomy series for similarly sized tumours. Therefore, partial nephrectomy is an acceptable and often preferred treatment for renal masses of >4 cm 24 . The first RAPN in Australia was performed in 2010 25 .…”
Section: Robotic Partial Nephrectomymentioning
confidence: 99%